Relationship between parasympathetic reactivity and oxidative stress in Polycystic ovary syndrome - Akhter, Ayesha; Ferdousi, Sultana; Sultana, Shamima; Mostafa, Musfika (Journal of Bangladesh Society of Physiologist, 2020)
Background: Polycystic ovary syndrome (PCOS) is a very common reproductive hormone disorder. Altered cardiovagal autonomic modulation and oxidative stress may predispose PCOS patients to increased cardiovascular morbidity. Objective: To assess the relationship between parasympathetic reactivity and oxidative stress in patients with PCOS. Methods: This crosssectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbagh, Dhaka from September 2018 to August 2019 on 35 newly diagnosed obese (BMI ≥25kg/m2) PCOS patients aged 20-35 years. Age and BMI matched 35 apparently healthy women were also enrolled as control. Three noninvasive conventional autonomic function tests, such as heart rate response to deep breathing, standing and the Valsalva maneuver, were used for evaluation of parasympathetic reactivity. For assessment of oxidative stress, plasma malondialdehyde level (oxidant) and plasma catalase level(antioxidant) were measured in all subjects by spectrophotometry. Data were expressed as mean± SD. For statistical analysis Independent sample “t” test, Pearson’s correlation test and multiple regression analysis were done as applicable. Results: In this study PCOS patients had significantly higher (p<0.01)resting heart rate, systolic and diastolic blood pressure than that of healthy control. But Expiration: Inspiration ratio, Expiration:Inspiration difference and 30:15 ratio during standing were significantly lower (p<0.001, p<0.01 and p<0.05 respectively) in PCOS compared to control. In addition, plasma catalase level was significantly lower (p<0.01)and plasma malondialdehyde level significantly higher (p<0.001) in PCOS in comparison to healthy control. Multiple regression analysis showed plasma catalase as a significant positive predictor (p<0.05) of the Valsalva ratio in PCOS. Also, Valsalva ratio showed significant negative association (p<0.05) with plasma malondialdehyde (p<0.01)in PCOS. Conclusion: Based on these results it is concluded that impaired parasympathetic reactivity showed inverse relationship with oxidative stress in PCOS. J Bangladesh Soc Physiol. 2019, December; 14(2): 48-55